A Study Of The Impact Of The Corrective Programme For The Very Poor Malnourished Preschool Children In Kelantan, Malaysia. - Yusoff, Haniah (2001)
The Corrective Programme for Malnourished Children (CPMC) is an ongoing national programme to combat problem of undernutrition especially among the very low socioeconomic group. It was launched by the Ministry of Health in 1989. The children will receive a basket of food every month which contain balance nutritional requirement such as rice, wheat flour, anchovy, green beans, sugar, formula milk, cooked oil, margarine, biscuits, multivitamin and iron supplement. Their weight and height were monitored every month and health education was given by the public health nurse to the parents in terms of food preparation and personal hygiene.